2000
DOI: 10.1111/j.1365-2621.2000.tb10597.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supercritical Carbon Dioxide and High Pressure on Lipoxygenase and Peroxidase Activity

Abstract: The effects of supercritical carbon dioxide (ScCO 2 ) treatment and high hydrostatic pressure treatment on the activities of lipoxygenase (LOX) and peroxidase (POD) were studied. Hydrostatic pressure treatment (240 MPa, 55°C, 15 min) of LOX and POD in 30% sucrose solutions without buffer led to approximately 80% and approximately 50% residual activity, respectively. Application of ScCO 2 (35.2 MPa, 40°C, 15 min for LOX and 62.1 MPa, 55°C, 15 min for POD) achieved approximately 35% LOX and approximately 65% POD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 20 publications
(4 reference statements)
0
24
0
Order By: Relevance
“…Some investigations showed that DPCD effectively inactivated various enzymes Balaban et al, 1991;Chen et al, 1992;Ishikawa et al, 1996;Tedjo et al, 2000;Park et al, 2002;Gui et al, 2006). In this study, the inactivation of LOX induced by DPCD was also measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations showed that DPCD effectively inactivated various enzymes Balaban et al, 1991;Chen et al, 1992;Ishikawa et al, 1996;Tedjo et al, 2000;Park et al, 2002;Gui et al, 2006). In this study, the inactivation of LOX induced by DPCD was also measured.…”
Section: Resultsmentioning
confidence: 99%
“…Ishikawa, Shimoda, Yonekura & Osajima (1996) reported that several enzymes, such as lipase, alkaline protease, acid protease and glucoamylase, were inactivated and their α-helix structures were decomposed after DPCD. DPCD resulted in total inactivation of LOX and peroxidase after 15 min at 55°C (Tedjo, Eehtiaghi, & Knorr, 2000). Park, Lee and Park (2002) achieved significant inactivation of LOX and PPO in carrot juice at a temperature as low as 5°C with DPCD treatment.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, enzyme stability and activity may depend on the enzyme species, the characteristics of the compressed fluid, the water content of the enzyme/support/reaction mixture, and the process variables involved, which means that very distinct effects can be achieved depending on the characteristics of the system under investigation (Chaudhary et al 1996;Kamat et al 1995;Kamat et al 1993;Kamat et al 1992;Taniguchi et al 1987;Tedjo et al 2000;Chen et al 1992;Ishikawa et al 1996;Oliveira et al 2006a;Oliveira et al 2006b;Gieβauf and Gamse 2000;Fricks et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…High pressure carbon dioxide (HPCD) is one of the non-thermal methods that have received considerable attention for potential applications in a number of food processing fields including inactivation of enzymes that can adversely affect the quality of food products (Damar & Balaban, 2006). HPCD treatment has been shown to be effective in inactivating pectinesterase, lipoxygenase, polyphenol oxidase (PPO) and peroxidase (POD) either in pure enzymatic solutions or in real food systems such as fruit juices (Balaban et al, 1991;Chen, Balaban, Wei, Marshall, & Hsu, 1992;Gui et al, 2007;Park, Lee, & Park, 2002;Tedjo, Eshtiaghi, & Knorr, 2000). These studies show that HPCD treatment can be effective in inactivating certain enzymes at temperatures which would normally not lead to significant thermal inactivation.…”
Section: Introductionmentioning
confidence: 99%